Development and application of a spray tip that enables electrocoagulation of a variety of tissues - Satomi Iwai; Shou Kobayashi; Shinji Torai; Eiji Kobayashi (Heliyon, 2023)
Background: Spray hemostasis is possible using a high-frequency power source from the tip of an electric scalpel; however, the difficulties regarding the uniformity and rapidity of the hemostasis surface remain. This study reports the development of a novel electrocoagulation device tip that can be used in endoscopic and robotic surgeries and can quickly coagulate and hemostat and easily adjust the extent of cauterization and hemostasis while minimizing the depth of thermal injury. Methods: The safety and efficacy of the hemostatic device were verified in a porcine model. A liver surface transection was conducted in vivo and the rapidity of the hemostatic effect of the device was observed. An extracted stomach, kidney, and liver were cauterized ex vivo by three operators with different surgical skills and the effects were analyzed pathologically. In addition, a sacrificed pig cadaver was used to achieve hemostasis at a renal transection site using the multi-spray endoscope tip. Results: An increase in the number of tip terminals expanded the cauterization surface and shortened the cauterization time. In parenchymatous organs, uniform cauterization was possible without increasing the depth of thermal injury. The cauterization depth did not depend on the operator's skill, and the spray coagulation was safe. The variable spray tip allowed for simple hemostasis during open and laparoscopic surgeries. Conclusions: This novel electrocoagulation device tip can be developed as a forceps that can change the spray range and can be used during laparoscopic and robotic surgeries.